WOMEN'S LEADERSHIP IN BRAZILIAN HISTORY: : MEMORIES, MATERIAL CULTURE, AND REPRESENTATIONS IN HISTORICAL MUSEUMS (Interdisciplinary Studies Journal, 2025)
This article presents the investigation (ongoing research) on education in historical museums and gender equality, in which priority is given to analyzing the cultural, political and social representations of women and how they are presented to the school public. In this sense, it is important to discuss the history of women/gender in a conception linked to gender museology, supporting readings of the world and cultural awareness in museum spaces. We highlight in this article, the reflection on three women, (Anita Garibaldi, Maria Quitéria and Eva Maria de Jesus (Tia Eva) in three historical museums in regions of Brazil, based on what is taught about them in museums, their representations and their stories of leadership. The collections of historical museums in Brazil: Museu do Ipiranga (São Paulo), Museu Anita Garibaldi (Laguna/SC), Museu José Antônio Pereira/MS with the theoretical approach to the construction of memory, of the possibilities and problematizations about teaching about Methodologically, it analyzes collections and exhibitions that are used in the educational sector of museums. Think about the educational practices of museums that deal with narratives, memories, images, contexts and that lead to the formation of historical consciousness, thinking of the historical museum as part of heritage. In other words, the aim is to analyze the historical-educational constitution of learning in museums, in which it is constituted as a 'place' of female belonging, contributing to the sharing of memories of a space, of feminine/feminist knowledge and gender equality.
Keywords: Women's Leadership; Female Representations; Museum Education